The collective storytelling organisational framework for social media use. (September 2021) - Davids, Zane; Brown, Irwin
Highlights: New IS theory that provides a better explanation of organisational social media use. High quality social media content fuel a successful collective storytelling process. A supportive social media strategy standardises organisational social media use. A co-creation process collectively generates valued social media services. Being consistently responsive lead to a more engaged and satisfied online community. Abstract: The organisational implementation and use of social media for online community engagement is plagued with many challenges. The result is managers being frustrated at not achieving their desired results. Despite an increase in social media research, it is evident that some critical aspects of social media use by organisations are left unexplained by existing theories. The purpose of this research study is to investigate how social media is used within organisations to engage with its online community. The grounded theory method (GTM) was used to develop a substantive theory that increases understanding of this phenomenon. Two organisations were selected as the case studies. Both are industry leaders in South Africa, with one being a prominent retailer with a visible social media presence and the other, being a leading university in South Africa, which is actively growing its social media presence. The results show that organisations enter a collective storytelling process with their online community. The need to reduce risk to reputation and improve on the levels of online community engagement are identified as reasons for this. The strategic alignment of the social media function and the organisational social media use characteristics set the backdrop for the collective storytelling process, while content quality influences the richness of this process. Challenges associated with the collective storytelling process lead to the development and refinement of the organisational social media strategy, which in turn helps to reduce risk to reputation and improve online community engagement.